Combined chemical-biological treatment of wastewater containing refractory compounds - Guo, Chenghong. (2008)
The combination of chemical and biological processes represents an effective and cost attractive method alternative to either chemical or biological means in wastewater treatments. The combined chemical and biological treatment processes have been successfully applied in treatment of wastewater containing refractory compounds. Microorganisms can degrade majority of organic pollutants, however, the chemical pre- treatment can enhance the biodegradability of refractory compounds. This dissertation provides an overview of the applications of the combined processes in the treatment of wastewater containing refractory compounds. The mechanisms of the processes, the process optimization, current applications and further development are discussed in this dissertation. The main conclusion is that the combined processes are useful when the biological treatment is limited because of toxicity or poor degradability of refractory pollutants.